Synthesis of Novel Stilbene–Coumarin Derivatives and Antifungal Screening of Monotes kerstingii-Specialized Metabolites Against Fusarium oxysporum - Ghislain Wabo Fotso; Bathelemy Ngameni; Thomas E. Storr; Bonaventure Tchaleu Ngadjui; Sibongile Mafu; G. Richard Stephenson (Antibiotics, 2020)
Fusarium is one of the most toxigenic phytopathogens causing diseases and reduced agricultural productivity worldwide. Current chemical fungicides exhibit toxicity against non-target organisms, triggering negative environmental impact, and are a danger to consumers. In order to explore the chemical diversity of plants for potential antifungal applications, crude extract and fractions from Monotes kerstingii were screened for their activity against two multi-resistant Fusarium oxysporum strains: Fo32931 and Fo4287. Antifungal activity was evaluated by the determination of minimum inhibitory concentration (MIC) by broth dilution of fermentative yeasts using kinetic OD600 nm reading by a spectrophotometer. The n-butanol fraction showed the best activity against Fo4287. We screened eleven previously reported natural compounds isolated from different fractions, and a stilbene–coumarin 5-[(1E)-2-(4-hydroxyphenyl)ethenyl]-4,7-dimethoxy-3-methyl-2H-1-benzopyran-2-one (1) was the most active compound against both strains. Compound 1 was employed as a nucleophile with a selection of electrophilic derivatizing agents to synthesize five novel stilbene–coumarin analogues. These semisynthetic derivatives showed moderate activity against Fo32931 with only prenylated derivative exhibiting activity comparable to the natural stilbene–coumarin (1), demonstrating the key role of the phenolic group.